A Fanconi-Bickel syndrome patient with a novel mutation and accompanying situs inversus totalis - Tuğba Taştemel-Öztürk; Berrak Bilginer-Gürbüz; Özlem Tekşam; Serap Sivri (The Turkish Journal of Pediatrics)
Fanconi-Bickel syndrome is a rare autosomal recessive disorder of carbohydrate metabolism, caused by mutations in the SLC2A2 gene, that codes for the glucose transporter protein 2 (GLUT2). The disease is characterized by proximal renal tubular dysfunction, impaired glucose and galactose utilization, and accumulation of glycogen in the liver and kidney. Signs and symptoms of Fanconi-Bickel syndrome begin in infancy and include failure to thrive, hepatomegaly, hypophosphatemic rickets, and short stature. Here in we report a Turkish Fanconi-Bickel syndrome case who also has situs inversus totalis and a novel mutation that has not been described before.